Исследование конструкторско-технологических решений создания тензомодулей датчиков давления - Иващенко, Е. А. (ХНУРЭ, 2009)
Basic principles of planning of pressure transformer are in-process formulated on the base of silicic integral transformer with the resilient element. The base construction of transducer is developed, which allows due to standardization of cabinet-type details and frame-clamping operations considerably to extend the area of the use of device, including as independent good.
Keywords: сенсорные сети; датчики давления; тензомодули